Radiobiology Experiments With Ultra-high Dose Rate Laser-Driven Protons: Methodology and State-of-the-Art - Chaudhary, Pankaj; Milluzzo, Giuliana; Ahmed, Hamad; Odlozilik, Boris; McMurray, Aaron; Prise, Kevin M.; Borghesi, Marco (Frontiers in Physics, 2021)
The use of particle accelerators in radiotherapy has significantly changed the therapeutic outcomes for many types of solid tumours. While protons are well known for sparing normal tissues and increasing the overall therapeutic index, carbon ions have been suggested to be particularly effective in the treatment of radio-resistant hypoxic tumours due to their higher Relative Biological Effectiveness (RBE) and Linear Energy Transfer (LET) values than protons. Cyclotrons generated FLASH protons delivery at a dose rate of 100 Gy/sec and above have shown excellent pre-clinical results due to the normal tissue sparing. Laser-driven proton acceleration methods can take dose delivery durations a step further by delivering Gy level doses in single or multiple pulses of picosecond duration even faster than FLASH dose rates. An extensive investigation of the radiobiology of laser-driven proton is not only necessary for future clinical application, but also offers the opportunity of accessing yet untested regimes of radiobiology where the dose is delivered to biological samples at dose rates exceeding, by many orders of magnitude, what is normally possible with conventional RF accelerators. This paper provides an updated review of the recent progress achieved in ultra-high dose rate radiobiology of laser-driven protons. We will briefly cover the methodology, dosimetry and the radiobiology of laser-driven protons.